Metacognition and its relationship with students' academic performance - Zulkiply, Norehan (2006)
This paper discusses metacognition, defined as thinking about one's own thinking, and its relationship to student's academic performance. A number of previous studies have shown that metacognition and intelligence were associated, and therefore suggested that students who have metacognition tend to be successful learners. This paper also reports on a study investigating the relationship between students' academic achievement and metacognitive awareness, which has been done a private secondary school in Kuching. An established instrument by Shraw and Anderson’s Metacognitive Awareness Inventory is used for the purpose of this study. Specifically, this study examined the relationship between student’s academic performance and each of the five components of metacognition regulation namely planning, information management strategies, comprehension monitoring, debugging strategies and evaluation. It also examined metacognition awareness in students across gender and different academic years. Overall, the findings revealed a significant positive relationship between student's academic performance and metacognitive awareness, a significant difference in metacognition awareness between Form 2 and Form 5 students, and no significant difference in metacognition awareness between male and female across all academic years. Some suggestions to develop metacognition in students are discussed, and possible directions for research on metacognition in learning process are proposed.